2015
DOI: 10.5465/amp.2013.0094
|View full text |Cite
|
Sign up to set email alerts
|

New Varieties of State Capitalism: Strategic and Governance Implications

Abstract: We analyze the new varieties of state capitalism in the 21st century and explore their implications in terms of both strategic and governance outcomes. We begin by discussing how the current theoretical perspectives conceptualize state-owned enterprises' strategic behavior. Then we introduce a stylized distinction between four broad, new varieties of state capitalism-wholly owned state-owned enterprises, the state as a majority investor, the state as a minority investor, and the state as a strategic supporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
335
2
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(355 citation statements)
references
References 89 publications
7
335
2
11
Order By: Relevance
“…While some studies have been critical, others have found that, in a competitive setting and under effective regulation, SOEs are generally just as efficient as private forprofit enterprises (Mühlenkamp, 2013). Recent studies of social enterprises have produced a similar result (Musacchio et al, 2015).…”
Section: Performance Of Hybrid Organizationsmentioning
confidence: 97%
“…While some studies have been critical, others have found that, in a competitive setting and under effective regulation, SOEs are generally just as efficient as private forprofit enterprises (Mühlenkamp, 2013). Recent studies of social enterprises have produced a similar result (Musacchio et al, 2015).…”
Section: Performance Of Hybrid Organizationsmentioning
confidence: 97%
“…Recent works on state-led capitalism have recognized this issue and have started to provide for subcategories (Musacchio et al, 2015). Given the emphasis on ownership patterns, this may provide for a useful classification with respect to corporate governance outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The new SOEs of the 21st century are not necessarily the same as the SOEs of the 20th century (Bremmer, 2010;Economist, 2012b). In other words, while most SOEs of the 20th century were the classic, Bstate-owned and state-controlled^firms, in the 21st century tremendous diversity exists among the SOE population (Bruton et al, 2015;CuervoCazurra, Inkpen, Musacchio, & Ramaswamy, 2014;Musacchio, Lazzarini, & Aguilera, 2015). Some of the new SOEs have substantial private participation in management and shareholding (Jiang, Peng, Yang, & Mutlu, 2015).…”
mentioning
confidence: 96%